M. Alexander Castrén's Grammatik der samojedischen Sprachen. - Castrén, M. Alexander (Matthias Alexander), 1813-1852.; Schiefner, Anton, 1817-1879. (St. Petersburg, Buchdruckerei der Kaiserlichen Akademie der Wissenschaften: [etc., etc], 1854)
No. 1 in v. 2 of a collection of his works. Mode of access: Internet.